The impact of government expenditure in agriculture and other selected variables on the value of agricultural production in South Africa (1983-2019): Vector autoregressive approach - Etian Ngobeni; Chiedza L. Muchopa (Economies, 2022)
South African agriculture has the potential to stimulate growth in other economic sectors, but dwindling budgetary allocations to agriculture over time and the nature of other impacting factors on the value of agricultural production have not received much attention in recent times. Therefore, the present study examined the effects of government expenditure in agriculture, annual average rainfall, consumer price index, food import value, and population on the value of agricultural production with a specific focus on government expenditure in agriculture for the period 1983 to 2019. Using the Johansen cointegration test, the results reveal that there is a long-run relationship among the variables. The Granger causality test results suggest that government expenditure in agriculture does not Granger cause the value of agricultural production. However, the two variables are linked through other variables in the model, such that an increase in government expenditure in agriculture, average annual rainfall, and population were shown to ultimately increase the value of agricultural production based on vector autoregressive (VAR) model analysis. In contrast, an increase in the consumer price index and food import value is detrimental to the value of agricultural production. These studies' findings have policy implications for increased government expenditure.
Keywords: 330; Granger causality; government expenditure in agriculture; Johansen cointegration; value of agricultural production; vector autoregressive